GESTATIONAL SAC TO CRL RATIO AS A PROGNOSTIC MARKER IN EARLY PREGNANCY: TWO CASE REPORTS - Ilkiv, Ivanna; Kucharska , Agata; Stanowska , Patrycja; Adler, Konrad; Gebert , Zuzanna; Zaręba , Agnieszka; Juszkiewicz , Dawid; Kiełczewski , Krzysztof; Fetner , Barbara; Dłużewska , Magdalena (International Journal of Innovative Technologies in Social Science, 2026)
The aim of this study was to assess whether the relationship between gestational sac (GS) size and crown–rump length (CRL) may have value in predicting early pregnancy outcome.We report two cases of early intrauterine pregnancy with initially normal ultrasound findings, including the presence of embryonic cardiac activity. Both patients underwent serial transvaginal ultrasound examinations in the first trimester, with measurement of GS, CRL and yolk sac, as well as derived indices including GS–CRL difference and GS/CRL ratio.In both cases, early scans were reassuring. However, in follow-up examinations the gestational sac failed to keep pace with embryonic growth, resulting in a progressive mismatch between GS and CRL. This preceded pregnancy loss despite previously normal viability parameters. One case was additionally complicated by a subchorionic hematoma, while in the second a relatively small gestational sac was noted before diagnosis of missed miscarriage.These cases suggest that an unfavorable GS–CRL relationship may precede early pregnancy loss even when cardiac activity is present. The observation is preliminary and requires confirmation in larger prospective studies.